Analisis Penyebaran Covid 19 Menggunakan Model SIR (Susceptible, Infected, Recovered) Di Provinsi Bali - Suniantara, I Gusti Ngurah Gede Agung; Gunantara, Nyoman; Sudarma, Made (Majalah Ilmiah Teknologi Elektro; Vol 22 No 1 (2023): (Januari - Juni) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2023.v22i01.P05, 2023)
The Corona Virus Disease 2019 (Covid-19) pandemic was announced by World Health Organization on March 11, 2020. World Health Organization explained that Coronavirus is a virus that can cause disease in animals and humans. The spread of the Covid-19 virus has spread to Indonesia and has spread to all provinces. The spread of COVID-19 can be modeled mathematically using the SIR model. The SIR model is divided into three compartments, namely susceptible individuals, infected individuals, and recovered individuals. SIR estimates can be checked for error rates using the MAPE method. The results of the SIR estimation in Bali Province obtained are that the Covid19 pandemic will end on August 09, 2024, the SIR model applied produces an error rate of 49%, the error rate is quite good because the MAPE value is between 20% and 50%. Key Words— COVID-19; SIR; MAPE.